Peran Proses Pembelajaran Dalam Pengembangan Kapabilitas Manufaktur Skala Menengah Dan Besar Di Jawa Timur - Lena Ellitan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
This study examines manufacturing capabilities from the perspective of resource-based view of the firm. It explores the role and capabilities in manufacturing firms that cannot be easily duplicated. Such resources and capabilities in manufacturing firms are formed by employees’ internal learning based on cross training and suggestion system, external learning from customer and suppliers, and proprietary processes and equipment developed by the firms. Based on data from 38 manufacturing firms in East Java, the paper empirically demonstrated that competitive advantage in manufacturing result from proprietary processes and equipment which, in turn, is driven by external and internal learning. In other words this study found that (1). Greater internal learning leads to more proprietary processes and equipment. (2) Greater internal learning leads to more proprietary processes and equipment (3). Greater proprietary process and equipment leads to higher competitive manufacturing performance. (4). The alignment between proprietary process and equipment and the manufacturing strategy leads to maximum competitive advantage.